Bacillus amyloliquefaciens GB03 augmented tall fescue growth by regulating phytohormone and nutrient homeostasis under nitrogen deficiency - Wang, Qian; Ou, Er-Ling; Wang, Pu-Chang; Chen, Ying; Wang, Zi-Yuan; Wang, Zhi-Wei; Fang, Xiang-Wen; Zhang, Jin-Lin (Frontiers in Plant Science, 2022)
Nitrogen is an important nutrient for plant growth and development. Soil microorganisms have been used to curb the imbalance between the limited content of natural environmental nitrogen and the pollution caused by increasing nitrogen fertilizer use in ecologically fragile areas. Bacillus amyloliquefaciens GB03 has been shown to confer growth promotion and abiotic stress tolerance in Arabidopsis thaliana. This study provided a new insight into the role of the plant growth-promoting rhizobacterium B. amyloliquefaciens GB03 as an initiator of defense against nitrogen deficiency in non-leguminous grass tall fescue (Festuca arundinacea). Two-week-old seedlings of tall fescue were grown with or without GB03 for 4 weeks under total nitrogen (3.75 mM NO3-) or low nitrogen (0.25 mM NO3-) treatment. Growth parameters, chlorophyll content, endogenous total nitrogen, total phosphorus content, and phytohormone content, including those of auxin indole-3-acetic acid, cytokinin, gibberellic acid, and abscisic acid, were determined at the time of harvest. Tall fescue grown in GB03-inoculated soil was more robust than the non-inoculated controls with respect to plant height, root length, plant biomass, chlorophyll concentration, and nutrient (total nitrogen and total phosphorus) contents under total nitrogen treatment. GB03 increased indole acetic acid content by 24.7%, whereas decreased cytokinin and abscisic acid contents by 28.4% and 26.9%, respectively, under a total nitrogen level. Remarkably, GB03 increased indole acetic acid content by more than 80% and inhibited abscisic acid production by nearly 70% under a low nitrogen level. These results showed, for the first time, that GB03 played a crucial role in mediating NO3–dependent regulation of tall fescue growth and development, especially revealing the mechanism of soil bacteria improve resistance to nitrogen deficiency stress in non-nitrogen-fixing species.